Bacteriological evaluation of sampled sachet water sold in Samaru-Zaria, Kaduna-State, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:The quality of drinking water is an important environmental determinant of health. Widespread production and consumption of inadequately processed or contaminated packaged drinking water can lead to waterborne disease outbreaks. To safeguard public health, it is important that available packaged water is duly registered and regularly analysed.Aim:This study was carried out to determine the bacteriological quality of ten selected brands of sachet water produced and sold in Samaru Zaria metropolis.Materials and Methods:From the brands of sachet water being sold in samaru, ten most popular brands were identified and selected based on patronage by consumers and distributors. A total of 20 samples, two from each of the ten brands of sachet water were bought from water vendors every fortnight for 1 month (may - june 2013).Results:The total coliform count ranged from 2-18+/100 ml. Isolates were identified to beKlebsiella spp., 0[40%] Proteus spp.,[30%]Pseudomonas spp.[20%]and Chromobacterium violaceum[10%]. All were negative for thermotolerant coliforms, Salmonella, Shigella and Vibrio cholera. Conclusion: The results of this study showed contamination with micro-organisms found naturally in water, soil or vegetation which indicates a problem with the overall quality of water production but showed no contamination with sewage or animal waste. Microbiological assessment of drinking water quality should be done periodically with the regulatory body National agency for food and drug administration and control (NAFDAC) ensuring good quality assurance and maintenance of internationally defined drinking water standards.